Effect of a Using PBL-based Chemical Equilibrium E-Module on Students’ Science Literacy Skills: A Quasy-Experimental Study in Indonesian High School - Nikmatusyadiah; Yerimadesi (Universitas Islam Indonesia, 2026)
Scientific literacy is a crucial competency in modern education. However, limited studies have examined its impact on science literacy within the Indonesian Phase F curriculum context. This research seeks to investigate the effect of using a problem- based learning (PBL) e-module on chemical equilibrium on the science literacy skills of Phase F students at SMAN 9 Padang. It employs a quasi-experimental method with a non-equivalent control group design. The population consists of Phase F students at SMAN 9 Padang, while the sample includes Class XI F3 (27 students) and Class XI F8 (27 students). The samples were selected through purposive sampling to meet the research criteria, namely students with relatively similar ability levels. The research instrument consisted of a test designed to measure students’ science literacy abilities. Data were analyzed using N-gain calculations, normality and homogeneity tests, as well as hypothesis testing. The findings indicate that the average N-gain in the experimental group (0.55) is higher than that in the control group (0.45). The results of the normality and homogeneity tests show that the data are follow a normal distribution and are homogeneous. Furthermore, the hypothesis testing using a t-test revealed that the obtained t-count value (2.3781) is greater than the critical t-table value (1.6747). These findings indicate that the use of a PBL-based chemistry equilibrium e-module provides a significant effect on enhancing students’ science literacy in high school.